2019
DOI: 10.1186/s13256-019-2215-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent spontaneous pneumothoraces and vaping in an 18-year-old man: a case report and review of the literature

Abstract: Background Primary spontaneous pneumothorax is a common disorder occurring in young adults without underlying lung disease. Although tobacco smoking is a well-documented risk factor for spontaneous pneumothorax, an association between electronic cigarette use (that is, vaping) and spontaneous pneumothorax has not been noted. We report a case of spontaneous pneumothoraces correlated with vaping. Case presentation An 18-year-old Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
1
36
0
3
Order By: Relevance
“…Second most common diagnosis included either organizing pneumonia/ Bronchiolitis obliterans with organizing pneumonia (BOOP)/ respiratory bronchiolitis (n = 12) [38][39][40][41][42][43][44][45][46] or lipoid pneumonia (n = 9) [11,[47][48][49][50][51]. In 4 cases vaping precipitated a pneumothorax [52][53][54] and in 2 exacerbated pre-existing asthma [55]. Other diagnoses included eosinophilic pneumonia (n = 4) [56][57][58][59], combination of organizing and lipoid pneumonia (n = 3) [40], hypersensitivity pneumonitis (n = 3) [46,60,61], diffuse alveolar hemorrhage (DAH) (n = 1) [62], acute respiratory distress syndrome (ARDS) (n = 1) [63], a combination of ARDS, organizing pneumonia and diffuse alveolar damage (DAD) (n = 1) [64], epiglottitis (n = 1) [65], and a possible EVALI on asthma grounds (n = 1) [46].…”
Section: Classification Of Casesmentioning
confidence: 99%
“…Second most common diagnosis included either organizing pneumonia/ Bronchiolitis obliterans with organizing pneumonia (BOOP)/ respiratory bronchiolitis (n = 12) [38][39][40][41][42][43][44][45][46] or lipoid pneumonia (n = 9) [11,[47][48][49][50][51]. In 4 cases vaping precipitated a pneumothorax [52][53][54] and in 2 exacerbated pre-existing asthma [55]. Other diagnoses included eosinophilic pneumonia (n = 4) [56][57][58][59], combination of organizing and lipoid pneumonia (n = 3) [40], hypersensitivity pneumonitis (n = 3) [46,60,61], diffuse alveolar hemorrhage (DAH) (n = 1) [62], acute respiratory distress syndrome (ARDS) (n = 1) [63], a combination of ARDS, organizing pneumonia and diffuse alveolar damage (DAD) (n = 1) [64], epiglottitis (n = 1) [65], and a possible EVALI on asthma grounds (n = 1) [46].…”
Section: Classification Of Casesmentioning
confidence: 99%
“…From 2012 to Aug. 30, 2019 (before publication of the CDC investigation), there were 30 publications [5][6][7][8][9][10][11][12][15][16][17][18][19][20]27,[29][30][31]34,[36][37][38][39][40][41][42][43][44][45][46] identifying a diverse array of vapingassociated pulmonary insults, with varying imaging and pathological findings, but no reported deaths (Table 1). From Sept. 1 to Oct. 30, 2019, an additional 13 publications 13,21,22,26,28,32,33,35,47,[51][52][53][54] were identified through our search strategy (Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patient observation 2 weeks after removing the tube from the chest confirmed the disappearance of pneumothorax. During the follow-up visit, he reported that he had stopped using all vaping products [13]. The described case is the first regarding the correlation between vaping and recurrent spontaneous pneumothorax.…”
Section: Resultsmentioning
confidence: 80%